2009
DOI: 10.1371/journal.ppat.1000424
|View full text |Cite
|
Sign up to set email alerts
|

Avian Influenza Virus Glycoproteins Restrict Virus Replication and Spread through Human Airway Epithelium at Temperatures of the Proximal Airways

Abstract: Transmission of avian influenza viruses from bird to human is a rare event even though avian influenza viruses infect the ciliated epithelium of human airways in vitro and ex vivo. Using an in vitro model of human ciliated airway epithelium (HAE), we demonstrate that while human and avian influenza viruses efficiently infect at temperatures of the human distal airways (37°C), avian, but not human, influenza viruses are restricted for infection at the cooler temperatures of the human proximal airways (32°C). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 52 publications
5
73
0
Order By: Relevance
“…A strain with relatively poor persistence at high temperatures could be assumed [31] to fare poorly during infection within a host, where internal temperatures can be high (e.g. 408C inside a duck [54,55]). …”
Section: Results (A) Quantifying Temperature-dependent Environmental mentioning
confidence: 99%
“…A strain with relatively poor persistence at high temperatures could be assumed [31] to fare poorly during infection within a host, where internal temperatures can be high (e.g. 408C inside a duck [54,55]). …”
Section: Results (A) Quantifying Temperature-dependent Environmental mentioning
confidence: 99%
“…Unlike human influenza viruses, which replicate efficiently in respiratory tracts where the temperatures range from 32°C in the upper respiratory tract to 37°C in lower respiratory tract (34,35), avian influenza viruses have adapted to replicate at the higher temperatures, 40 to 41°C, of the avian enteric tract (36). The upper respiratory tract provides a large surface area of susceptible cells and is usually the initial site of infection and likely the predominant site of influenza virus replication in mammalian species (37).…”
Section: Figmentioning
confidence: 99%
“…Scull et al demonstrated that amino acid substitution Glu627Lys in PB2 does not entirely account for conferring temperature dependency in mammalian cells. It was suggested that viruses bearing avian or avianlike surface glycoproteins have a reduced capacity to establish productive infection at the temperature of the human proximal airways (36).…”
Section: Figmentioning
confidence: 99%
“…Culture systems of differentiated primary epithelial cells from human and animal airways, especially derived from the trachea, provide valuable in vitro models for characterization of cellular tropism and infectivity of influenza viruses (24)(25)(26)(27)(28)(29)(30)(31). Differentiated tracheal epithelial cell cultures offer numerous advantages, including greater control of experimental conditions and the ability to study epithelial cell function in the absence of other cell types, such as cells representing submucosal glands, all of which can contribute valuable information for in vivo studies.…”
mentioning
confidence: 99%